A case of Brugada syndrome - Dr. C. K. DAS (Medico Research Chronicles, 2020)
A 25-year male came to OPD who had Upper Respiratory Tract Infection with fever for 3 days followed by sudden unconsciousness while on duty. He had spontaneous recovery from unconsciousness approximately after 1 hour.